Making sense of Kant's 'critique of pure reason' : an introduction - Pendlebury, Michael (London [England] : Bloomsbury Academic, 2022)
"Tackling Kant's seminal enlightenment text, Critique of Pure Reason, remains key for every student of modern philosophy. Michael Pendlebury distils his breadth of experience teaching Kant's first Critique to provide a short, accessible introduction that reveals its enduring inspirations, challenges and ideas to thinkers grappling with contemporary philosophical issues. Clarifying and making sense of Kant's account of perception, cognition, space, time, substance, causation, actuality, objectivity, and the presuppositions and limits of human knowledge makes Critique of Pure Reason digestible for all students, including those approaching it for the first time. Making Sense of Kant's Critique of Pure Reason concentrates on key portions of the text that are essential to a basic understanding of Kant's project, providing an introduction that situates his ideas as solutions to philosophical problems. The book offers a sympathetic account of Kant's theory of a priori cognition alongside its application for readers new to Kantian philosophy, and uses select quotations from the original text to foreground Kant's Critique independent of subsequent debates and interpretations. Pendlebury makes sense of Kant's own views and arguments, creating a stimulating read that provides a useful starting point for further study."--
Preface A Note on Citations of and Quotations from Kant's Works -- 1. Background. 1.1 The Basic Structure of Our World ; 1.2 Knowledge and Reality ; 1.3 The Critique of Pure Reason -- 2. The Preface and the Introduction: Two Types of Metaphysics. 2.1 A Science of Metaphysics? ; 2.2 A Priori Cognition ; 2.3 The Analytic/Synthetic Distinction ; 2.4 Synthetic a Priori Judgments and Knowledge ; 2.5 Transcendental Philosophy -- 3. The Transcendental Aesthetic: Sensibility, Space, and Time. 3.1 Intuitions, Appearances, and the Forms of Sensibility ; 3.2 The Presentation of Space ; 3.3 The Reality of Space ; 3.4 The Presentation and Reality of Time -- 4. The Introduction to the Transcendental Logic: Sensibility and Understanding -- 5. The Metaphysical Deduction: Judgments, Concepts, and Categories. 5.1 Concepts and Judgments ; 5.2 Forms of Judgment and Categories ; 5.3 Synthesis -- 6. The Analogies and the Second Postulate: Fundamental Principles About Substance, Causation, Interaction, and Actuality. 6.1 Experience and Objectivity ; 6.2 The First Analogy: Substance ; 6.3 The Second Analogy: Causation ; 6.4 The Third Analogy: Interaction ; 6.5 The Second Postulate: Actuality -- 7. The Transcendental Deduction: Why Intuitions Fall Under the Categories. 7.1 The Challenge ; 7.2 Apperception and Judgment: Why Intuitions Must Fall Under Categories ; 7.3 Interlude ; 7.4 Figurative Synthesis: Why Intuitions Can Fall Under Categories ; 7.5 Dreams, Hallucinations, and Seemings -- 8. The Schematism: How Intuitions Fall Under Categories. 8.1 Transcendental Schemata as Criteria. 8.2 Sensible and Empirical Schemata and the Synthesis of Imagination ; 8.3 Transcendental Schemata and Forms of Imaginative Synthesis -- 9. The Dialectic: The Limits of Speculative Reason. 9.1 Illusions of Transcendent Metaphysics ; 9.2 The Paralogisms of Pure Reason: The Soul ; 9.3 The Antinomy of Pure Reason: Nature ; 9.4 The First Antinomy: A Bounded World? ; 9.5 The Third Antinomy: Freedom and the Necessity of Nature ; 9.6 The Ideal of Pure Reason: God ; 9.7 The Regulative Function of Ideas -- 10. Taking Stock. 10.1 Making Sense of Transcendental Idealism ; 10.2 Kant's Achievement Further Reading References -- Index of Citations of Passages in the Critique of Pure Reason Index of Concepts, Topics and Names.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Kant, Immanuel, -- 1724-1804.; Knowledge, Theory of; Causation; Reason; Electronic books